O papel da amônia sobre as alterações comportamentais, neuroinflamação e apoptose em um modelo experimental de acidemia metilmalônica. - Gabbi, Patricia (2017)
Methylmalonic acidemia is an autosomal recessive metabolism biochemically characterized by a deficiency in the activity of the mutase methylmalonyl-CoA and the tissue accumulation of methylmalonate (MMA). In this acidemia, also occurs the accumulation of propionyl-CoA, which causes the inhibition of the metabolism of ammonia by urea cycle, leading to hyperammonemia. Clinically, this acidemia is characterized mainly by neurological disorders, including seizures and cognitive impairment. The data published in the article revealed that mice with acute treatment of MMA (0.66 mmol/2 uL) intracerebroventricularly (i.c.v) and an intermediate dose of NH 4 Cl (6 mmol/g) showed an increase in the duration of seizures induced by MMA. The administration of NH4Cl (6 mmol/g) also induced an increase of nitrite/nitrate (NOx), as well as the production of mitochondrial ROS over oxidation of 2,7-dichlorofluorescein diacetate (DCFH-DA) DCFH, GS and followed by inhibition GAD. The NH4Cl plus MMA administration did not alter cytokine levels, plasma fluorescein extravasation, or neuronal damage. However, it potentiated DCF-RS levels, decreased the ΔΨ potential, reduced MTT, inhibited SDH activity, and increased Na+,K+-ATPase activity. NH4Cl also altered the GABA cycle characterized by GS and GAD activity inhibition, [3H] flunitrazepam binding, and GABA release after MMA injection. Since ammonia increased cerebral excitability of animals treated with MMA, it was objective this study to evaluate the ammonia role in development neural and glial of young mice after MMA administration, as well as to verify cognitive performance of these animals. The data presented in the manuscript demonstrated the results of MMA administration (2.5 μmol/g; injected intracisternally) or NaCl (2.5 μmol/g; i.c) on the first day of life and NH4Cl (7.5 mmol/g i.p.) or NaCl (0.9%; i.p.) on the second day of life of mice. From 21° to 33 ° or 40° to 52° days of age, the animals were evaluated for behavioral tasks such as radial maze test and high cross test. The levels of tumor necrosis factor-alpha (TNF-α), interleukin 1-betha, and DCFH were measured in cerebral cortex, striatum and hippocampus of mice with 21 and 40 days of life. The radial maze test showed that the animals injected with MMA and NH4Cl presented a worse performance in the working memory test, but not in the reference memory test in animals with 21 and 40 days of life. The animals showed no anxiety behavior. In addition, MMA and NH4Cl administration increased levels of TNF-α, DCFH in the cerebral cortex, hippocampus and striatum of mice with 21 and 40 days of life. The Interleukin 1β levels increased in cerebral cortex and striatum but not in hippocampus increased both in mice at 21 and 40 days of life.Considering the data presented, it is suggested that the changes in ROS and reactive nitrogen species (RNS) levels elicited by ammonia alter the glycine/glutamate/GABA cycle and contribute to MMA-induced excitability. Furthermore, increased ROS production is related to an enhanced brain inflammatory process in a precocious period of development, leading to a learning delay in the animals treated with MMA. Thus, it is plausible to propose that ammonia contributes with cerebtral dysfunction in methylmalonic patients, favoring the appereance of neurological symptoms.